EFFECT OF ORGANIZATIONAL COMMITMENT AND EMPLOYEE EMPOWERMENT AND REWARD AND PUNISHMENT OF MOTIVATION BPJS SERVICES AND PERFORMANCE OF EMPLOYEES IN HOSPITAL ABDUL WAHAB SJAHRANIE SAMARINDA, INDONESIA - et.al, Ratri Nugrahaningsih, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this research is to analyze and prove the effect of organizational commitment, employee empowerment, reward and punishment to the motivation of BPJS services as well as the performance of employees at the Hospital Abdul Wahab Sjahranie Samarinda. This research is observational research with cross sectional research design, the data collection techniques using the survey method. The population of this research is 1700 employees of the hospital Abdul Wahab Sjahranie Samarinda While the research sample uses the formula Slovin with a total sample of 324 respondents. The analysis tool uses a statistical method of Structural Equation Modeling with the approach WarpPLS 6.0. The results of this research can be concluded that the influential organizational commitments have a positive and significant influence on the motivation of BPJS services, the organizational commitments are negatively and insignificant to employee performance, employee Empowerment negatively and Significantly Affect the service motivation BPJS, employee empowerment positively and insignificant impact on employee performance, reward and punishment positive and significant impact on the service motivation BPJS, reward & punishment positive and significant impact on performance, BPJS service motivation has positive and significant impact on the performance of employees at the Hospital Abdul Wahab Sjahranie Samarinda.